1989
DOI: 10.1159/000281478
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Electrostimulation of the Pelvic Floor: Primary Therapy in Female Stress Incontinence?

Abstract: A prospective evaluation of the therapeutic effect of neuromuscular electrical pelvic floor stimulation was performed in 55 women with urinary stress incontinence awaiting surgical repair. Chronic stimulation was applied anally or vaginally by an integrated plug electrode for a median of 5.4 months. After therapy, 68% of the patients were continent or had improved so such that the planned operation was cancelled. At 2-year follow-up, the persisting success rate after electrostimulation was reduced to 56%, 31% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
3

Year Published

1997
1997
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(49 citation statements)
references
References 5 publications
2
44
0
3
Order By: Relevance
“…However, as pure stress UI can be easily controlled, this was explored more speci®cally. Some have reported [29] that after 2 years of treatment, 56% of women presenting with stress UI are improved using only physiotherapy. Previous reports suggest that >70% of women treated with conventional surgery recover fully or are much improved after 5 years [28,30].…”
Section: Discussionmentioning
confidence: 99%
“…However, as pure stress UI can be easily controlled, this was explored more speci®cally. Some have reported [29] that after 2 years of treatment, 56% of women presenting with stress UI are improved using only physiotherapy. Previous reports suggest that >70% of women treated with conventional surgery recover fully or are much improved after 5 years [28,30].…”
Section: Discussionmentioning
confidence: 99%
“…The reflex stimulation of pelvic nerves inhibits detrusor, regulates local blood flow, increases cognitive function and increases adrenergic activity while decreasing cholinergic activity 1,17,[19][20][21] . Delay in the reaction of pelvic floor reflexes and/or weakness of the pelvic floor muscles can cause stress incontinence so the electrical stimulation of the pelvic floor may restore the neuromuscular activity 5) . Since the current spreads, more motor units can be affected and a stronger contraction can be obtained 5) .…”
Section: Discussionmentioning
confidence: 99%
“…Even though genuine stress incontinence is often treated surgically, the use of rehabilitation methods are increasing in use. Pelvic floor exercises, biofeedback and pelvic floor muscle are some of the conservative methods advised for adult urinary stress incontinence before invasive procedures 4,5) . It has been reported that electrical stimulation may be an effective alternative method to surgical treatment with success rates of 6-90% in the treatment of genuine stress incontinence, but it has not been widely used because of a lack of knowledge about its physiology and technical principles [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(56) observed the effectiveness of the mixed UI therapy using medications to reduce overactive bladder together with a pelvic floor rehabilitation program. The use of ES can improve symptoms (33,57,58) up to 77% and may provide a 40% reduction in costs if performed instead of surgery. Regardless of the technique employed, we found (Tables 5 and 6) a high success rate in this treatment, which provided data increasing the reliability of this therapy.…”
Section: Parameters Assessedmentioning
confidence: 99%